Pembuatan Minyak Gosok Penghangat Tubuh, Penghilang Bengkak Dan Pegal Linu Menggunakan Bahan Alami Tumbuhan, Di Desa Bingkat Kecamatan Pegajahan Kabupaten Serdang Bedagai Sumatera Utara - Melati Yulia Kusumastuti; Pebrinawanti Br Saragih; Cut Fatimah; Firman; Najwa Putri Utami; Nirina Putri Andini (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
This community service activity aims to improve the community’s knowledge and skills in making natural-ingredient massage oils as both an alternative health product and a business opportunity. The program was implemented in Bingkat Village, Pegajahan Subdistrict, Serdang Bedagai Regency, with the primary target being housewives who are members of the PKK group. The main challenges faced by the community partners include high reliance on chemicalbased products, limited understanding of the use of medicinal plants, and a lack of productive activities that support family economies. Implementation methods included outreach sessions, training, hands-on practice, and guidance in making massage oil using natural ingredients such as lemongrass oil and nutmeg seed oil. In addition, participants were also provided with training in packaging, business management, and basic marketing. The results of the activities showed an increase in the community’s knowledge and skills in processing natural ingredients into massage oil products that are safe, effective, and economically valuable. This program is expected to promote community selfreliance and increase family income through the development of businesses based on local potential.